Answer:
[tex]\displaystyle average=\frac{1}{2(e-1)}[/tex]
Step-by-step explanation:
Average Value of a Function
Given a function g(x), we can compute the average value of g in a given interval (a,b) with the equation:
[tex]\displaystyle average=\frac{1}{b-a}\int_{a}^{b} g(x)dx[/tex]
We use the given data
[tex]\displaystyle average=\frac{1}{e-1}\int_{1}^{e} \frac{lnx}{x}dx[/tex]
We now compute the indefinite integral with a u-substitution
[tex]\displaystyle I=\int \frac{lnx}{x}dx[/tex]
We'll use the substitution u=lnx, du=dx/x. Then
[tex]\displaystyle I=\int u.du[/tex]
Integrating
[tex]\displaystyle I=\frac{u^2}{2}[/tex]
Since u=lnx
[tex]\displaystyle I=\frac{ln^2x}{2}[/tex]
The average value is
[tex]\displaystyle average=\frac{1}{e-1}\left|\frac{ln^2x}{2} \right|_1^e[/tex]
[tex]\displaystyle average=\frac{1}{e-1}\left(\frac{ln^2e}{2}-\frac{ln^21}{2} \right )[/tex]
Since lne=1, and ln1=0
[tex]\displaystyle average=\frac{1}{e-1}\left(\frac{1}{2}-0 \right )[/tex]
[tex]\displaystyle average=\frac{1}{2(e-1)}[/tex]